PEMERTAHANAN LEKSIKAL TANAMAN OBAT TRADISIONAL UNTUK PENYAKIT ANAK PADA KOMUNITAS REMAJA DI BALI : KAJIAN SEMANTIK EKOLINGUISTIK - Rasna, I Wayan; Binawati, Ni Wayan S. (Bumi Lestari Journal of Environment, 2012)
This research aims at investigating: 1) the lexical farm of traditional medical plants for children deseas according to Usada Rare; 2) young generations knowledge about the lexical forms of traditional medical plants for children’s diseases in accordance with Usada Rare manuscripts; 3) the uses of the lexical forms of traditional medical plants in adults speech. The setting of this study is the province of Bali, consisting of eight regencies and one city government, with the total number of samples of 225 adults and 2545 traditional headers. The samples of the study were determined by using purposive quota sampling technique. The dates about the lexical forms were collected by means of documentations method and note-talking technique. The data about the adults knowledge as to the traditional medical plants were obtained through structured questionnaire and lexical competency test. The data concerning the adults speech were gained through speaking test. Then, the data were analyzed descriptively. The result of the study shows that; 1) the lexical forms of the traditional medical plants according to Usada Rare were 122 types, which are classified into general and specific material ; 2) the young generations knowledges about the lexical forms can be categorized into : a) the young generation having very strong believe towards traditional medications and having very strong maintainance as to the lexical forms of medical plants, such as adult in Klungkung regency 247 (49,40%); Karangasem 226 (45,20%), and Bangli 210 (42%); b) The group of community having a strong confidence about modern medication will have a weaker maintainance about the lexical forms of medical plants, such as Denpasar 60 individuals ( 12%), Badung 65 people (13%), and Buleleng 83 persons ( 16,60%). The uses of lexical forms in speech were limited to the contexts of curing deseases. Suggestions are directed to health department, Bapedal, Dishutbun, and Documents Centre of Balinese Culture, to take care, socialize and conserve the environment together for the sake of keepingthe health of the nature, culture and community.
Keywords: maintainance; lexical; medical plants; ecolinguistics